2017
DOI: 10.1007/s10555-017-9718-5
|View full text |Cite
|
Sign up to set email alerts
|

From biomarkers to therapeutic targets—the promises and perils of long non-coding RNAs in cancer

Abstract: Biomarker-driven personalized cancer therapy is a field of growing interest, and several molecular tests have been developed to detect biomarkers that predict, e.g., response of cancers to particular therapies. Identification of these molecules and understanding their molecular mechanisms is important for cancer prognosis and the development of therapeutics for late stage diseases. In the past, significant efforts have been placed on the discovery of protein or DNA-based biomarkers while only recently the clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 211 publications
1
58
0
Order By: Relevance
“…This group of RNAs has an average length of 22 nucleotides that do not code for proteins (non-coding RNA). miRNAs attach mRNAs by complementary base binding and can post-translationally control the expression of proteins in cells [12,40]. miRNAs affect a variety of molecular processes and are necessary for the proper development of tissues, drug resistance and immune response [41][42][43][44].…”
Section: Micrornas As Novel Emerging Biomarkersmentioning
confidence: 99%
“…This group of RNAs has an average length of 22 nucleotides that do not code for proteins (non-coding RNA). miRNAs attach mRNAs by complementary base binding and can post-translationally control the expression of proteins in cells [12,40]. miRNAs affect a variety of molecular processes and are necessary for the proper development of tissues, drug resistance and immune response [41][42][43][44].…”
Section: Micrornas As Novel Emerging Biomarkersmentioning
confidence: 99%
“…Emerging evidence has demonstrated that lncRNAs represent a novel class of pivotal regulators of gene functions and multiple physiological events (Wang et al, 2018(Wang et al, , 2019Yamazaki et al, 2018). They have been found to maintain sub-cellular architecture, stabilize protein complex, and participate in multiple biological processes (Del Vecchio et al, 2018;Gutschner et al, 2018;Liu et al, 2018;Wang et al, 2019;Yan et al, 2019;Yu et al, 2019). First discovered in 2007, nuclear enriched abundant transcript 1 (NEAT1) plays crucial roles both in carcinogenesis (Klec et al, 2019) and non-cancerous diseases, such as neurodegeneration and inflammation (Prinz et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Long noncoding RNA (lncRNAs) are nonprotein coding transcripts longer than 200 nucleotides and have been reported to participate in a variety of biological processes,including regulation of gene expression, subcellular architecture, and stabilization of protein complexes 3 . Mechanistically, lncRNAs sponge many different types of miRNAs, acting as competing endogenous RNAs (ceRNAs) to display its function.…”
Section: Introductionmentioning
confidence: 99%